PUPCYCLE II coastal Oregon in-line hyperspectral optical data - Sacchidanandan Pillai (PANGAEA, 2025)
We present hyperspectral particulate absorption and attenuation data as measured using a SeaBird AC-S as part of the PUPCYCLE II cruise. Data were derived from ship-based observations aboard the R/V Sally Ride from 28 May to June 11, 2023, as part of a program studying the Phytoplankton response to the UPwelling CYCLE (PUPCYCLE II) along the Northern part of the California Current System. This data was used to investigate changes in phytoplankton assemblage composition, photo-physiology and productivity across upwelling gradients in the northern California Current System. . Differences in hyperspectral signatures appeared to reflect variable age and source of the upwelling water masses, and a potential signature of iron and silicic acid co-limitation across our study area, as inferred from differences in macro- and micronutrient concentrations, and molecular diagnostic signatures. Our results demonstrate high-resolution hyperspectral data extquotesingles utility in observing phytoplankton taxonomic and photo-physiological variability in dynamic upwelling systems.